PENGARUH KEMAMPUAN MANAJERIAL KEPALA SEKOLAH, DISIPLIN KERJA, DAN KOMUNIKASI INTERPERSONAL TERHADAP KINERJA GURU - Nova Gita; Lilik Kustiani; Riril Mardiana Firdaus (Jurnal Riset Pendidikan Ekonomi, 2018)
Objective of the research to reveal the influence of the principal managerial ability, work discipline, and interpersonal communication affects the teacher performance. The study uses a quantitative approach to the type of ex post facto research. The population is 06 teachers of SMK PGRI Malang. A sample of 58 respondents. The technique of collecting data using questionnaires and documentation. Analysis of data using multiple linear regression results show that (1) There is a significant influence managerial skills of principals, work discipline, and interpersonal communication simultaneously on teacher performance, (2) There is a significant influence managerial capability Principal partially on teacher performance (3) No effect on the performance of teachers' work discipline, (4) there is a significant influence interpersonal communication partially on teacher performance.